BIOTECHNOLOGY AS MAIN DIRECTION OF DEVELOPMENT OF PULP AND PAPER INDUSTRY OF RUSSIA AND THE WORLD - D. Sheikin (Publishing House of the State University of Management, 2016)
The article analyses the global trends and prospects of development of pulp and paper industry. It assesses the directions of application of biotechnology in forestry and pulp and paper industry. The paper presents forecasts of growth and market development of products created using biotechnology. It identifies goals and objectives for the development of biotechnology pulp and paper industry in Russia.